2000
DOI: 10.1139/e99-091
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of sea-surface temperature, salinity, and sea-ice cover in the northern North Atlantic during the last glacial maximum based on dinocyst assemblages

Abstract: Past sea-surface conditions over the northern North Atlantic during the last glacial maximum were examined from the study of 61 deep-sea cores. The last glacial maximum time slice studied here corresponds to an interval between Heinrich layers H2 and H1, and spanning about 20-16 ka on a 14C time scale. Transfer functions based on dinocyst assemblages were used to reconstruct sea-surface temperature, salinity, and sea-ice cover. The results illustrate extensive sea-ice cover along the eastern Canadian margins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(61 citation statements)
references
References 66 publications
8
53
0
Order By: Relevance
“…Rochon et al (1999, text fig. 9a, 35) extended the known modern distribution of Islandinium minutum into the north temperate realm of the North Atlantic Ocean; and fossil assemblages from Late Glacial Maximum sediments off western Norway are in agreement with this distribution, showing Islandinium minutum (<10%) co-occurring with the tropical to temperate species Lingulodinium machaerophorum (about 4-7%) (de Vernal et al, 2000). Andersen et al (1991) also found small numbers of I. minutum and L. machaerophorum co-occurring in Weichselian deposits from Norway.…”
Section: Islandinium Minutummentioning
confidence: 64%
“…Rochon et al (1999, text fig. 9a, 35) extended the known modern distribution of Islandinium minutum into the north temperate realm of the North Atlantic Ocean; and fossil assemblages from Late Glacial Maximum sediments off western Norway are in agreement with this distribution, showing Islandinium minutum (<10%) co-occurring with the tropical to temperate species Lingulodinium machaerophorum (about 4-7%) (de Vernal et al, 2000). Andersen et al (1991) also found small numbers of I. minutum and L. machaerophorum co-occurring in Weichselian deposits from Norway.…”
Section: Islandinium Minutummentioning
confidence: 64%
“…The presence of seasonal sea ice in the region between 20 and 16 cal. ka BP has also been inferred from dinoflagellate cysts analysed from core MD95-2010(de Vernal et al, 2000 and by analysis of planktonic foraminifera assemblages (Weinelt et al, 2003). Thus, the laminations might be the product of a possibly annual cycle where in winter/cooler periods sea ice cover and a reduced input from iceberg melting lead to lower density and thinner layers.…”
Section: Sedimentation Processesmentioning
confidence: 96%
“…Thermohaline circulation in the Norwegian-Greenland Sea was also less vigorous during H1 (Rasmussen et al, 1997;Rasmussen and Thomsen, 2002). Delineation of past permafrost patterns in Europe during intense cold periods, such as the LGM and the Younger Dryas, bears out the association of increased permafrost extent with a cold North Atlantic and abundant pack ice (Renssen and Vandenberghe, 2003) especially in winter (de Vernal et al, 2000). The extremely cold and dry climate that was prevalent during the Gschnitz stadial implies that similar conditions may have existed about 16 000 yr ago.…”
Section: Glacier Advances In the Alps During Heinrich Event 1 125mentioning
confidence: 99%